Epidemiology, pattern and economic burden of pediatric fall injury at tertiary neurological institute in Kathmandu. - Gajuryal,Sharad Hari (2021)
ABSTRACT: Background: Trauma represents major global health concern. Falls are the second leading cause of accident or unintentional deaths worldwide after road traffic accident. Despite the large number of accidental injuries in children especially fall injuries in Nepal and its impact, there is at present no country wide study examining its epidemiology and economic burden. Therefore, there is gap in the literature on epidemiological data as well as economic burden from Nepal concerning fall injury in children. Methods: A cross-sectional prospective study was conducted to analyse epidemiology, pattern as well as economic burden of pediatric fall injury at Annapurna Neurological Institute & Allied Sciences. The eligibility criteria included all pediatrics patients who presented to the hospital with a history of fall injury between 1st November 2020 to 30th August 2021. Results: 153 patients were identified who met the inclusion criteria. The mean age of patient who sustained fall injury was 7.09 years ( with SD +-4.2) The most common age group sustaining fall injury was 1-5 years (n=65) followed by 6-10 years (n=59). Fall injury in the study participants was more common in males than females. Fall from height was most common mode of injury (n=101) out of which fall from stairs and window was common mode 38.86% of patient had common clinical pattern, i.e. head injury with 2.61@motality among overall participants. Average cost for patient undergone conservative treatment was Nrs.42,530($355) whereas patients undergone surgical intervention was Nrs.2,78,909($2325). Conclusion: This study concluded that demographic data for patients sustaining a pediatric fall injury at Annapurna Neurological Institute & Allied Sciences is consistent with data from other developing and developed Countries. We found that the majority of patients with fall injury were from age group 1-5 years. The high incidence of pediatrics fall injury indicate the need for more supervision during playing and identification for specific risk factors for these injuries injuries in our setting. The study shows that these epidemiological parameters could be a useful tool to identify burden and research priorities for specific type of injuries. This can help in reducing economic burden as well as reducing the alternation of quality of life in productive age group.